Brønsted Acid Catalyzed Friedel–Crafts Alkylation Reactions of Trifluoromethyl-α,β-ynones with Indoles - Sasaki, Shigeru; Ikekame, Yuta; Tanayama, Manabu; Yamauchi, Takayasu; Higashiyama, Kimio (Synlett, 2012)
The successful development of a Brønsted acid catalyzed Friedel–Crafts alkylation reaction between trifluoromethyl-α,β-ynones and indoles has been described. The reaction is catalyzed by benzoic acid (5 mol%), with the indoles adding to the carbonyl carbon of the trifluoromethyl-α,β-ynones producing the corresponding 1,2-addition products as trifluoromethyl propargyl alcohols in high yields. Furthermore, treatment of the product with indoles in the presence of trifluoroacetic acid (10 mol%) afforded trifluoromethyl-functionalized unsymmetrical bis(indolyl)propynes in high yields.
Keywords: Brønsted acid; trifluoromethyl-α,β-ynones; indoles; trifluoromethyl propargyl alcohols; bis(indolyl)propynes